Simplify the following expression without using a calculator:
3 2 5 + 2 2 2 + 3 2 5 − 2 2 2
Inspiration for this problem comes from this video .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the expression equal x
3 2 5 + 2 2 2 + 3 2 5 − 2 2 2 = x (A)
And let the expressions within the 1st and 2nd cube roots equal a and b respectively
a = 2 5 + 2 2 2 , b = 2 5 − 2 2 2
Hence we can rewrite (A) as
a 3 1 + b 3 1 = x
By cubing both sides, we can simplify the expression
\(\begin{aligned}
x^3 & = a + 3a^\frac{2}{3}b^\frac{1}{3} + 3a^\frac{1}{3}b^\frac{2}{3} + b \\ & = a + b + 3a^\frac{1}{3}b^\frac{1}{3}(a^\frac{1}{3} + b^\frac{1}{3})
\end{aligned}\)
We now notice that we can replace a 3 1 + b 3 1 with x here since x = a 3 1 + b 3 1 . Hence we have
x 3 = a + b + 3 a 3 1 b 3 1 x
And since a + b = 5 0 and a b = − 3 4 3 we have
\(\begin{aligned}
x^3 & = 50 + 3(-343)^\frac{1}{3}x \\ & = 50 + -21x
\end{aligned}\)
By solving the following cubic x 3 + 2 1 x − 5 0 = 0 by testing small values of x , we notice that x = 2 .
This can be verified using Wolfram Alpha .
Note: we also have 2 imaginary solutions to the cubic above, these are extraneous solutions .
Problem Loading...
Note Loading...
Set Loading...
Let a = 3 2 5 + 2 2 2 and b = 3 2 5 − 2 2 2 . Then a b = 3 ( 2 5 + 2 2 2 ) ( 2 5 − 2 2 2 ) = 3 2 5 2 − 2 ⋅ 2 2 2 = 3 − 3 4 3 = − 7 (Honestly, I was in a car and did use my phone to calculate this and suspected 7 × 7 × 7 = 3 4 3 ). Then we have:
( a + b ) ( a 2 − a b + b 2 ) ( a + b ) ( ( a + b ) 2 − 3 a b ) ( a + b ) 3 + 2 1 ( a + b ) x 3 + 2 1 x − 5 0 ( x − 2 ) ( x 2 + 2 x + 2 5 ) ⟹ x = a 3 + b 3 = 2 5 + 2 2 2 + 2 5 − 2 2 2 = 5 0 = 0 = 0 = 2 Let x = a + b By rational root theorem Note that x 2 + 2 x + 2 5 = 0 has no real root.
Reference: Rational root theorem